(untitled) (Research, Society and Development, 2022)
The puerperium is the period of the pregnancy cycle that corresponds to the regression of the physiological changes of pregnancy in the female body. It starts right after delivery of the placenta and ends around six weeks postpartum. It is necessary to strengthen the importance of the nurse’s puerperal consultation, with a view to qualified care and comprehensive health care for mothers and newborns in Primary Care. Thus, the objective of this study is to strengthen the importance of qualified nursing care in the puerperal consultation in primary care. The study is an integrative literature review, with a qualitative character, carried out between the period of August and November 2021. Of the subjects covered in the studies, two had a greater prominence, where 71.42% dealt with the puerperal home visit and 57.14% addressed breastfeeding in the puerperal period. This study identified the importance of the role of nursing professionals in the puerperium, the implementation of programs and incentives for knowledge about the postpartum period, which should be increasingly present in Primary Care, to monitor, strengthen and guide the woman in this very special period, but which also often generates doubts and fears.